The Introduction of Mathematic Concept in Early Childhood Education: HOTS Skill Stimulation - Feri Faila Sufa; M Hery Yuli Setiawan (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2021)
Mathematics is important for human life, including for early childhood development. Introducing mathematical concepts from an early age provides many opportunities for success in human development. However, introducing mathematics is not just a child who can count and recognize various geometric shapes and follow certain patterns. The purpose of this study is to explore the ability of mathematical thinking patterns in children aged 4–6 years in cognitive development in stimulating high-level cognitive development. The method used in this research is descriptive quantitative and qualitative approaches. and the results showed that children are less stimulated to think to a higher level that can stimulate children to think rationally and solve their own problems. Mathematics learning is still in a formal setting and is predominantly using children's worksheets, so that children's interest is reduced. The results of this study recommend that learning mathematics involves more early childhood and raises interest and provides stimulation so that children can develop cognitive thinking in mathematics through reasoning and problem solving.